Improvement of penning ion sources - Bizyukov, A.A.; Bobkov, Vl.V.; Kashaba, A.Y.; Sereda, K.N. (Вопросы атомной науки и техники, 2000)
It is shown that the loss of a longitudinal symmetry of magnetic field distribution in respect to the centre of the Penning discharge system causes change of electrostatic potential distribution in the discharge gap leads to appearance of asymmetry of current magnitude to the cathodes of the Penning cell, change of magnitude of current density and energy distribution of the ion beam extracted in a longitudinal direction. The use of an inhomogeneous magnetic field which is longitudinally asymmetrical concerning electrodes of the system allows to increase current efficiency of Penning ion sources from 0,2 to 0,55.